2019
DOI: 10.3389/fnbeh.2019.00052
|View full text |Cite
|
Sign up to set email alerts
|

Affiliation, Aggression, and Selectivity of Peer Relationships in Meadow and Prairie Voles

Abstract: Relationships between adult peers are central to the structure of social groups. In some species, selective preferences for specific peers provide a foundation for consistent group composition. These preferences may be shaped by affiliation toward familiar individuals, and/or by aversion to unfamiliar individuals. We compared peer interactions in two vole species that form selective preferences for familiar same-sex individuals but differ in mating system. Prairie voles (Microtus ochrogaster) form pair bonds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 47 publications
5
82
3
Order By: Relevance
“…Female degus are also known to share burrows with multiple, often genetically unrelated peers [25][26][27]29,30,32,40] (in some cases even cohabitating with unrelated species [40]). As a point of contrast, prairie voles reside with only familiar pair mates or family members [41] and tend to great strangers aggressively [42]. When the two species were directly compared using a partner preference test, prairie voles have been found to spend almost all of their time near or huddling with a familiar partner [43], while degus spend their time near and huddling with partners and strangers, exhibiting no average preference for either [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female degus are also known to share burrows with multiple, often genetically unrelated peers [25][26][27]29,30,32,40] (in some cases even cohabitating with unrelated species [40]). As a point of contrast, prairie voles reside with only familiar pair mates or family members [41] and tend to great strangers aggressively [42]. When the two species were directly compared using a partner preference test, prairie voles have been found to spend almost all of their time near or huddling with a familiar partner [43], while degus spend their time near and huddling with partners and strangers, exhibiting no average preference for either [24].…”
Section: Discussionmentioning
confidence: 99%
“…Female degus are also known to share burrows with multiple, often genetically unrelated peers [25][26][27]30,31,33,48] (in some cases even cohabitating with unrelated species [48]). As a point of contrast, prairie voles reside with only familiar pair mates or family members [49] and tend to great strangers aggressively [50].…”
Section: Discussionmentioning
confidence: 99%
“…In social interaction tests of female meadow voles across day lengths, we found that SD-housed females interacted with novel conspecifics more than LD housed females, including both affiliative social contact and aggressive interactions (Lee et al, 2017). Increased social interaction between voles in winter may be further facilitated by social experience, as pair-housed SD meadow voles sniff, groom, and huddle with novel conspecifics more than individually-housed meadow voles (see 2.2.6).…”
Section: Meadow Voles: Behaviormentioning
confidence: 93%
“…Congruent with these findings, SD meadow vole females are more active in an open field, and spend more time in the center than do LD females (Reitz, 2014). Time spent investigating a novel conspecific in the social interaction test is classically used as a measure of anxiety (File and Seth, 2003), and SD meadow vole females are more interactive than LD females in this test (Lee et al, 2017).…”
Section: Meadow Voles: Behaviormentioning
confidence: 99%
See 1 more Smart Citation